Barista Competency Test Judging from Interpersonal Communication - Saidul Alam; Dewi Kurniawati (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Coffee shops in Indonesia are starting to grow significantly. America Starbucks was also present in Indonesia in 2001 because they saw a huge opportunity in Indonesia. Currently, coffee shops have mushroomed all over Indonesia, including the Medan City. The Medan City as one of the big cities in North Sumatra Province has many coffee shops which are usually used as a gathering place for young people. There are many coffee-based beverage service providers in Medan City, which of course has an impact, namely market competition. The purpose of this research is to find out barista competency test judging from interpersonal communication. The approach used in this research is a qualitative approach. In this study using primary and secondary data. The primary data from this research is interpersonal communication used by barista in creating customer satisfaction. Secondary data in this research can be in the form of a study of articles or books written by experts. The results showed that occur in the field between barista and customers through interview and observation data, this shows a pattern of interactive communication, where the interaction begins with greeting or welcoming from the barista to the order taking process using self service. All communication processes carried out by the barista are based on service standards.